Treaty Law Agreement International in National Law - Dina Paramitha Hefni Putri (International Journal of Educational Research Excellence (IJERE), 2023)
Source: Many formal laws are used by judges to decide a case. What just? The answer is that there are five sources of formal law that can be used by judges, i.e., laws, customs, treaties, jurisprudence, and doctrine. Usually, the judge decides a case based on laws, agreements, international law, and jurisprudence. If it turns out no, there is a source; that's what can be done to give an answer about the law, then searching for the opinions of scholars or knowledge of the law Knowledge law is source law, but no law like the Constitution has strength binding. So, you can just say that source law is many formal laws used by judges to decide a case, called laws, agreements, treaties, and jurisprudence. Treaty as Agreement International in the National Legal System Article 11 of the 1945 Constitution of the Republic of Indonesia only authorizes the president, with the authority of the DPR RI, to make agreements with other countries. creation and validation agreement internationally. Deep-gap regulation legislation in Indonesia causes diversity methods look to international law as well as inconsistency practice court national to application law international. Until moment this, there is not yet an explanation normative that can finish polemic practice inconsistency.